2014
DOI: 10.1093/mnras/stu364
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the ‘outliers’ track of the radio–X-ray correlation in X-ray binaries based on a disc–corona model

Abstract: The universal radio-X-ray correlation (F R ∝ F b X , b ∼ 0.5 − 0.7) has been found for a sample of black-hole X-ray binaries (BHBs) in their low/hard states, which can roughly be explained by the coupled model of jet and radiatively inefficient advection dominated accretion flow. However, more and more 'outliers' were found in last few years, which evidently deviate from the universal radio-X-ray correlation and usually show a much steeper correlation with an index of ∼ 1.4. Based on simple physical assumption… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 92 publications
3
25
0
Order By: Relevance
“…Recently, MeyerHofmeister & Meyer (2014) proposed an explicit form of such an efficient solution (see also Cao, Wu & Dong 2014;Huang, Wu & Wang 2014) by arguing that thermal photons from a weak, cool disc in the innermost regions of an otherwise inefficient accretion flow would be responsible for enhancing the seed photons available for Comptonisation, and hence the hard X-ray flux (in the context of this model, the 'radio quiet' track corresponding to the initial decline of the 2008 outburst of H1743-322 is better described as 'X-ray bright'). The condensation of hot, optically thin accreting gas into an inner, cool, keplerian disc is predicted above a critical mass accretion rate if thermal conduction and Compton cooling are properly accounted for in the equations of energy and mass exchange Liu, Meyer & Meyer-Hofmeister 2006;Liu et al 2007).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Recently, MeyerHofmeister & Meyer (2014) proposed an explicit form of such an efficient solution (see also Cao, Wu & Dong 2014;Huang, Wu & Wang 2014) by arguing that thermal photons from a weak, cool disc in the innermost regions of an otherwise inefficient accretion flow would be responsible for enhancing the seed photons available for Comptonisation, and hence the hard X-ray flux (in the context of this model, the 'radio quiet' track corresponding to the initial decline of the 2008 outburst of H1743-322 is better described as 'X-ray bright'). The condensation of hot, optically thin accreting gas into an inner, cool, keplerian disc is predicted above a critical mass accretion rate if thermal conduction and Compton cooling are properly accounted for in the equations of energy and mass exchange Liu, Meyer & Meyer-Hofmeister 2006;Liu et al 2007).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…In this way the accretion energy is released in the corona as thermal energy and eventually emitted away via inverse Compton scattering. By studying the energy balance of the disc and the corona, Huang et al (2014) solved the structure of the cold accretion disc. However, they can not self-consistently determine the temperature of the corona T and the Compton scattering optical depth τ, which are two very important quantities for determining the shape of the Compton emergent spectrum.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, T and τ should be solved independently for determining the Compton emergent spectrum. In Huang et al (2014), it is argued that the observationally inferred value of τ is in the range of ∼ 0.1 − 0.8, then through their calculation, τ = 0.5 is fixed to solve T for fitting this radio/X-ray correlation. In our model, we do not fix the value of τ.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that the correlation of L R ∝ L ∼1.4 X may be resulted by the transition of the accretion flow from the radiatively inefficient accretion flow, ADAF, to the radiatively efficient accretion flow, disc-corona system, with increasing the mass accretion rate (Coriat et al 2011;Gallo et al 2012, for discussions), which is later quantitatively interpreted by several authors with the disc-corona + jet model (e.g. Qiao & Liu 2015;Huang et al 2014;Meyer-Hofmeister & Meyer 2014). However, we note that the statistical significance of the aforementioned two tracks, i.e., the 'universal' correlation and the steeper correlation is still questioned (Gallo et al 2014(Gallo et al , 2018.…”
Section: Introductionmentioning
confidence: 99%